Effect of Adenotonsillectomy on Ambulatory Blood Pressure in Pediatric Obstructive Sleep Apnea: 6-Month Follow-up Study. (May 2019) - Kang, Kun-Tai; Chiu, Shuenn-Nan; Lin, Che-Yi; Weng, Wen-Chin; Lee, Pei-Lin; Hsu, Wei-Chung
Objective: To investigate 24-hour ambulatory blood pressure changes 6 months after surgery among children with obstructive sleep apnea. Study Design: Prospective interventional study. Setting: Tertiary medical hospital. Subjects and Methods: Children aged 4 to 16 years with symptoms of obstructive sleep apnea (apnea-hypopnea index >1) were recruited. All children underwent adenotonsillectomy and postoperative polysomnography overnight. The 24-hour ambulatory blood pressure was measured before and 6 months after surgery. Results: The study cohort enrolled 124 children: mean (SD) age, 7.3 (3.1) years; 73% boys. After surgery, the apnea-hypopnea index significantly decreased from 13.3 (18.1) to 3.3 (7.2) events per hour ( P < .001). Overall systolic blood pressure and diastolic blood pressure were not significantly different following surgery, while daytime systolic blood pressure was slightly increased (114.3 to 117.3 mm Hg, P < .01) postoperatively. The hypertensive group (n = 43) exhibited significantly decreased levels of overall diastolic, nighttime systolic, and nighttime diastolic blood pressure ( P < .05), and 54% of hypertensive children became nonhypertensive after surgery. The nonhypertensive group (n = 81) showed slightly increased levels of nocturnal overall systolic, daytime systolic, and nighttime systolic blood pressure. A generalized linear mixed model revealed that children with hypertension had a greater decrease in systolic and diastolic ambulatory blood pressure during the daytime and nighttime (all P < .05) than those without hypertension. Conclusions: Ambulatory blood pressure changes after adenotonsillectomy among children with obstructive sleep apnea are minimal. The decrease in ambulatory blood pressure after surgery is more prominent for hypertensive children than nonhypertensive children.